Assessing Biosecurity Risks for the Introduction and Spread of Diseases Among Commercial Sheep Properties in New South Wales, Australia, Using Foot-and-Mouth Disease as a Case Study - Fountain, Jake; Woodgate, Robert; Rast, Luzia; Hernández-Jover, Marta (Frontiers in Veterinary Science, 2018)
Sheep production systems are a major industry in Australia, with a gross value of roughly $4.66 billion; 87.3% of which is attributable to export markets. Exotic diseases such as Foot-and-mouth disease (FMD) are a potential threat to the viability of Australia’s export market. Previous outbreaks of FMD in developed countries, and challenges in the management of onshore biosecurity, signify the importance of on-farm biosecurity in controlling disease transmission. This study aims to investigate the risk of disease introduction and spread among New South Wales (NSW) sheep properties using FMD as a case study and draw recommendation for the industry. Exposure and a partial consequence assessments, using scenario trees and Monte Carlo stochastic modelling, were conducted to identify pathways of introduction and spread and calculate the probabilities of these pathways occurring. Input parameters were estimated from data obtained during qualitative interviews with producers and scientific literature. According to the reported practices of sheep producers and assuming each pathway was carrying the FMD virus, the exposure assessment estimates the median (5-95%) probability of FMD exposure of sheep on a naïve property to be 0.619 (0.541-0.698), 0.151 (0.085-0.239), 0.235 (0.153-0.324) and 0.710 (0.619-0.791) for introduction through new stock, wildlife, carriers (humans, dogs and vehicles) and neighbors, respectively. The spread assessment estimated the median probability of FMD spreading from an infected sheep property to neighboring enterprises to be 0.603 (0.504-0.698). A similar probability was estimated for spread via wildlife (0.523; 0.404-0.638); and a lower spread probability was estimated for carriers (0.315; 0.171-0.527), sheep movement (0.285; 0.161-0.462) and dead stock (0.168; 0.070-0.312). The sensitivity analysis revealed that introduction of an FMD-infected sheep was more influential for exposure via new stock than isolation practices. Sharing adjacent boundaries was found to be the most influential factor for exposure and spread between neighboring enterprises and to a lesser extent, hygiene practices were found to have the most influence on exposure and spread through carriers. To minimize the potential risk of FMD introduction and spread between sheep properties, maintenance of boundary fences, identification of infected animals before introduction to the property and hygiene and disinfection practices should be improved.